Correlation and assessment of coronary artery luminal stenosis: Post-mortem computed tomography angiogram versus histopathology. (March 2020) - Chainchel Singh, Mansharan Kaur; Abdul Rashid, Saiful Nizam; Abdul Hamid, Suzana; Mahmood, Mohd Shah; Feng, Siew Sheue; Mohd Nawawi, Hapizah; Omar, Effat
Highlights: Postmortem Computed Tomography Angiography (PMCTA) using water-based contrast was performed. Contrast media was injected through vessels of the neck. This method yielded comparable results to other methods of PMCTA. It has high specificity in coronary artery stenosis diagnosis. Its advantage is negating additional incision other than the usual autopsy cut. Abstract: Background: Post-mortem Computed Tomography (PMCT) allows non-invasive or minimally invasive detection of findings that may or may not be visible during conventional autopsy, however, it does not allow the investigator to draw any conclusions regarding patency of the vessel's lumen. To address this deficiency, Post-mortem Computed Tomography Angiography (PMCTA) utilizing different contrast media and techniques have been introduced with various studies looking at the correlation between PMCTA, autopsy (gross) findings and coronary artery histology in diagnosing coronary artery disease. Objectives: The aim of this study is to investigate the sensitivity and specificity of PMCTA in diagnosing coronary artery stenosis using water-based contrast media introduced though the vessels of the neck, compared to the gold standard of diagnosis i.e. gross and histological evaluation of the coronary artery. Method: This was a cross sectional study of 158 arterial sections involving 37 subjects recruited from the National Institute of Forensic Medicine (IPFN), Hospital Kuala Lumpur (HKL). An unenhanced PMCT was performed followed by PMCTA using water-based contrast media introduced though the vessels of the neck. Coronary artery stenosis was determined using multiplanar reconstructionD while the degree of stenosis was determined by calculating the percentage of luminal diameter divided by the diameter of the vessel internal elastic. Results: The analysis of PMCTA and histopathology examinations revealed a sensitivity of 61.5%, specificity of 91.7%; positive predictive value (PPV) of 40.0% and negative predictive value (NPV) of 96.4%. Conclusion: PMCTA utilizing water-based contrast introduced though the vessels of the neck yielded similar results as other methods and techniques of PMCTA. We would therefore conclude that PMCTA utilizing this technique could be used to assess the degree of calcification and the presence of significant stenosis.